2018
DOI: 10.3233/wor-182788
|View full text |Cite
|
Sign up to set email alerts
|

Young, vulnerable and uncertain: Young workers’ perceptions of work health and safety

Abstract: Our findings contribute to our understanding of young workers' perceptions of work health and safety. Although young workers could identify their concerns about particular health and safety related issues at work, they lacked the confidence to report their concerns and had limited information about where to go for help. The research suggests that there is a need to empower young people to report WHS concerns to their employer and provide structures and processes that encourage reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Young and less experienced, as well as temporary workers have been found to have an increased risk of workplace injury [9]. All of the patients involved in this study were aged >21 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Young and less experienced, as well as temporary workers have been found to have an increased risk of workplace injury [9]. All of the patients involved in this study were aged >21 years.…”
Section: Discussionmentioning
confidence: 99%
“…It is a global concern; about 11.2 million U.S. workers were found to suffer from UE-MSDs, and the annual incidence was found to increase [1]. Ma et al [1] and other investigators reported that construction [9] and automobile manufacturing industrial workers [10] had the highest prevalence of UE-MSDs. These diseases affect millions of healthcare and office workers, as well [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young employees' OSH risks are typically associated with lack of physical, cognitive and emotional development; lack of experience; lack of holistic understanding; lack of information and training; inappropriate attitudes and ignorance of OSH matters [11,[18][19][20][21]. Most often, young employees take risks either unconsciously or because of ignorance, or because they lack the courage and confidence to mention any risks or issues they notice or to apply for compensation [22][23][24].…”
Section: Young Employeesmentioning
confidence: 99%
“…What a bright idea" is an interactive booklet aimed at students from 14 to 18 years old addressing Occupational Safety and Health (OSH) topics. Bearing in mind that this particular target is a risk group for occupational fatigue and work accidents, the main objective determined for the educational resource was to increase students' awareness, including the ones with visual impairment or blindness, of OSH in their daily and professional lives; and, in the long term, to raise levels of safety at work and to decrease the number of occupational accidents and diseases among young workers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%